Risk Factor of Vitamin-D Deficiency for Urinary Tract Infections in Women at Reproductive Age - Almazini, Mohammed A.; Almazini, Amal Abdul-Imam (Scientific Journal of Medical Research, 2024)
Background: Urinary tract infections (UTIs) are common health infections in women with high complications. Many of the worldwide population suffer from vitamin D deficiency (VDD) due to insufficient exposure to sunlight. The relationship between VDD and resistance antibiotics isolates on UTI from women of different ages did not study in Basrah city for years. Aim: The present study aim to find the effect of VDD and resistance antibiotic isolates on UTIs in women of reproductive age. Methods: The samples were collected from September 2022 to January 2023 from outpatients of gynecology clinics and private clinics in Basrah city. A total of 70 samples were collected from females and 60 samples from males suffering recurrent UTI of different ages. The concentration of vitamin D is determined by using the Cobas e411 analyzer. In addition, the identification of bacterial isolates and antibiotic sensitivity is determined using a VITEC device. Results: This study included 130 midstream urine samples obtained from 70 females and 60 males. The ages of these patients ranged between 18 and 72 years. These samples were cultured on primary media, and then the identification of these unknown bacteria was done. The current study showed that the infections in females were significantly higher than in males. Infection was found to be significantly higher in the age group of 31 to 50 years than in the other age groups, followed by the age groups of 18 to 30 years. This study showed that E. coli is the most prevalent bacteria isolated from UTI patients, followed by Pseudomonas aeuroginosa. They occur mainly in females as compared to males, especially in the age group between 31 and 50 years. We sought to identify the prevalence of vitamin D3 deficiency among different ages. The deficiency of vitamin D levels in women was 82%. The levels of deficiency were significantly higher in the age group 25 to 34 years is 71.1%, followed by 15 to 24 years is 63.2%, and 35 to 45 years is 50%, with a mean 24 ± 6.8 years. In addition, we found isolates of E.coli have multidrug resistances. Conclusion: Our current study revealed that there is a clear correlation between women who suffer from VDD and UTIs, whether severe or frequent infection at reproductive age and this affects their fertility and pregnancy. In addition, the study showed that E. coli is the most prevalent bacteria isolated from UTI patients, followed by Pseudomonas aeuroginosa. There was a significant relationship between a decrease of serum vitamin D levels and the severity of urinary incontinence among reproductive-aged women. Our study demonstrates that a significant frequency of multidrug-resistant E. coli. In addition, imipenem was an appropriate drug to treat infections caused by these uropathogens. These findings may aid physicians in the management of UTI infections.